Chapter 1 The multifaceted picture of transdisciplinarity in marine research - Grünhagen, Caroline (Taylor & Francis, 2023)
Chapter 1 = The Swiss psychologist Jean Piaget is considered responsible for coining the term transdisciplinarity' in the 1970s, defining it as a higher stage after the interdisciplinary relations. To date, transdisciplinarity research is a growing field in academia, but still there is no uniform definition. In this book chapter, we explore how the term 'transdisciplinarity' is used in marine research including different fields like quantitative ecology and modeling, marine social science or marine conservation. We used a quantitative full-text analysis of peer-reviewed journal publications from 1992 to 2021, ensuring to include most recent contributions to the analysis. A total of over 6000 publications could be identified, about 500 of these focusing on marine realm. We applied an agglomerative hierarchical cluster analysis (program R) to consider relative frequencies of significant conceptual words within the transdisciplinary landscape. Multiple research clusters have been identified and further divided regarding the study background (e.g., meta-analysis, case study, theory).